Sistem Pakar Diagnosa Penyakit Pada Pernafasan Ayam Broiler Menggunakan Metode Forward Chaining - Wariputra, Yegi Fahrian (STMIK KAPUTAMA, 2020)
Broiler breeding business is fairly rapid development, so many are interested in cultivating. The rapid development of the livestock business is due to the large number of broiler markets. However, there are several factors that inhibit the cultivation of broilers, one of which is susceptible to disease that results in farmers experiencing material losses. with the rapid development of technology today, a multi-user website-based expert system has been created so that it can be used by many users. So the purpose of writing this research proposal is to design an expert system application to be able to diagnose diseases in chicken breathing, to help lay farmers.